Afrikansk skönlitteratur på svensk bokmarknad 1961–1981: Bo Cavefors Bokförlag och Afrika berättar RAGNI SVENSSON - Svensson, Ragni (Tidskrift för litteraturvetenskap, 2015)
African Fiction on the Swedish Market 1961–1981: Bo Cavefors Publishing Ltd. and the ”Afrika berättar” (”Africa Speaks”) Series This article examines the selection, marketing and reception of contemporary African fiction on the Swedish book market of the 1960s and 70s, through the case of a book series called ”Afrika berättar”, launched by Bo Cavefors Publishing, Ltd. Bo Cavefors was the Swedish publisher of writers such as Wole Soyinka, Ngu˜gı˜ wa Thiong’o and José Luandino Vieira. The article discusses the way in which these literary works were received from the perspective of current African politics. In addition, it considers the essential role of the publisher’s networks, such as freelance editors and translators in launching the series.